WIND ENERGY CONVERSION SYSTEM USING MAXIMUM POWER POINT TRACKING TECHNIQUE ‐ A COMPREHENSIVE SURVEY - Mohsin Ali Koondhar; Majid Ali; Muhammad Usman Keerio; Abdul Khalique Junejo; Imtiaz Ali Laghari; Sadullah Chandio (Applied Engineering Letters, 2021)
Over the past decade, wind power generation (WPG) has focused on energy generation, and much research is being done on renewable energy (RE), especially wind energy (WE). WE guarantee environmentally friendly power generation and help to meet national energy needs due to the declining trend of renewable resources. In this article, various Maximum Power Point Tracking (MPPT) techniques proposed for wind energy conversion system (WECS) modeling control management strategies and efficient wind power generation (WPG) from available sources have been discussed. In addition, a comparative survey of various familiar soft methods is accorded for an easy power system with the wind. At last, a cost‐effective investigation arrived for MPPT techniques found on (a) Saving of energy, (b) period of profit, (c) generated income, (d) cost, (e) capacity utilization aspect, and (f) solidity.